Self-Management dan Monitoring Kadar Glukosa Darah sebagai Penguatan Pilar Pengendalian Diabetes Melitus Tipe 2 - Dwi Novitasari; Adita Silvia Fitriana; Awal Tunis Yantoro; Afresa Bias Putri Enarga (Yayasan Inspirasi El Burhani, 2022)
Introduction: Diabetes Mellitus Type 2 DM (T2DM) is a metabolic disorder that accounts for 90% to 95% of all cases of DM. The success of T2DM therapy in controlling blood glucose with self-management can be influenced by individual characteristics, knowledge, health status, health system, and selection of anti-diabetic drugs. Self-management of DM patients is the attitude that patients apply to their understanding of DM, such as controlling diet, physical activity, medication adherence, and glucose management. Education by health workers about basic information on controlling glucose levels and the prevention of complications will improve the self-management of T2DM patients. Objective: This Community Service Program (CSP) aims to increase knowledge, self-management, and control of glucose levels in T2DM patients. Method: This CSP method uses lectures with leaflet media, discussions, questions and answers, and interviews, covering the preparation to evaluation stages individually. Measurement of self-management using the Diabetes Self-management Questionnaire (DSMQ). PCM partner is an Integrated Service for the Elderly in Tipar Kidul Village, Ajibarang. Result: The results of this CSP are that the blood glucose levels of CSP participants have an average blood glucose value of 244.8 mg/dl. As many as 26 (86.3%) are in the uncontrolled and hyperglycemic categories. The result was that the participants' blood glucose levels were 244.8 mg/dl, and 26 (86.3%) were in the uncontrolled or hyperglycemic category. Participants' self-management had a mean value of 37.4, included in the high or good level, and 19 (63%) were in the sufficient category. Conclusion: The outputs of this CSP activity are leaflets as educational media, intellectual property rights certificates of educational brochures, and publications in CSP journals.